2019
DOI: 10.1186/s12862-018-1340-9
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of gene expression diversity during domestication of animals and plants

Abstract: BackgroundThe genetic mechanisms underlying the domestication of animals and plants have been of great interest to biologists since Darwin. To date, little is known about the global pattern of gene expression changes during domestication.ResultsWe generated and collected transcriptome data for seven pairs of domestic animals and plants including dog, silkworm, chicken, rice, cotton, soybean and maize and their wild progenitors and compared the expression profiles between the domestic and wild species. Intrigui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 66 publications
3
40
1
Order By: Relevance
“…In contrast with the nucleotide diversity, however, we did not find a significant reduction in the diversity of gene expression. While such a reduction is reported for annual crops such as rice (5.1% reduction; Liu et al ., ) or common bean (18% reduction; Bellucci et al ., ), it might be a result of the generally weaker domestication syndrome in perennial plants. However, an important limitation of our result is the restricted number of samples used for the expression analysis, and further observations might provide a more robust outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the nucleotide diversity, however, we did not find a significant reduction in the diversity of gene expression. While such a reduction is reported for annual crops such as rice (5.1% reduction; Liu et al ., ) or common bean (18% reduction; Bellucci et al ., ), it might be a result of the generally weaker domestication syndrome in perennial plants. However, an important limitation of our result is the restricted number of samples used for the expression analysis, and further observations might provide a more robust outcome.…”
Section: Discussionmentioning
confidence: 99%
“…During evolution, the accuracy and efficiency of stress defence has been predestining the success of a particular plant species. This natural process was disturbed by domestication and conventional breeding, which diminished biological variation and resulted in the production of highyield, high-input cultivars with decreased environmental acclimation ability (Liu et al 2019). Based on transcriptome data it was shown that domestication and artificial selection affected the pattern of variation in gene expression throughout the genome and decreased the expression diversity across several examined animal and plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Given the impoverished state of the Xochimilco axolotl population, critically endangered and having suffered dramatic reductions in population size for many years [ 16 , 17 ], the wild populations could no longer reflect the variation of the wild source from which domestic populations arose. Breeding management strategies have shaped genetic variation of laboratory animal populations, causing in some cases large genetic differences plausibly not only between natural and laboratory animals, but also among laboratory strains, that can affect experimental reproducibility, including studies of gene expression [ 7 , 8 , 35 ]. The genetic differences found here need to be further investigated to address whether this variation is affecting biological processes.…”
Section: Discussionmentioning
confidence: 99%